(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This article proposes to present a reflection concerning the relationship between the image and the word and its multiple consequences observed throughout the historical, artistic and cultural journey since the Renaissance, through the nomenclatures of the garments. The city will be the stage for the permanence of many voices built over several stories and which will be registered in dictionaries from the 17th century onwards, in different regions of current Europe. Through the survey of a volume of nomenclatures that involve the sociocultural universe surrounding garments, textile materials and know-how, the construction of a specific area of knowledge is verified in the treated period: Fashion. The methodology addresses the study of different images of the arts, as well as ancient and contemporary texts regarding the history of Fashion and the history of images, where texts sew broader meanings through the intermidiality between words and representations. The terminologies studied were lexicographically defined and organized into three main groups: fashion, space/ time and society. Between words and images, we find a material world whose iconographic representation carries broader meanings, creating historical and cultural windows that allow contemporaneity to become effective as spectators of the past, as recipients of memories.